2002
DOI: 10.1046/j.1365-2044.2002.02602.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microfiltration in decreasing propofol‐induced pain*

Abstract: SummaryIn a randomised, double-blinded, two-centre trial we evaluated the effect of a microbiological filter (SuporÒ, Pall Life Sciences) on propofol injection pain. We studied 336 unpremedicated adult patients, who graded pain experienced during induction of anaesthesia with propofol on a 4-point verbal rating scale. Use of the microfilter reduced both the incidence and severity of propofol injection pain (p < 0.001). Incidence of severe pain in the filter group was 2.4% compared with 16.6% in the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
(22 reference statements)
0
14
1
Order By: Relevance
“…Presently, the most commonly used method in clinical practice is a combination of drugs to prevent propofol injection pain, of which lidocaine is the most widely used. However, several studies have proven that lidocaine may increase the diameter of propofol particles and thus inflict pulmonary embolism 11. Additionally, a combination of lidocaine and propofol may damage the stability of propofol emulsion, thus limiting the effect of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the most commonly used method in clinical practice is a combination of drugs to prevent propofol injection pain, of which lidocaine is the most widely used. However, several studies have proven that lidocaine may increase the diameter of propofol particles and thus inflict pulmonary embolism 11. Additionally, a combination of lidocaine and propofol may damage the stability of propofol emulsion, thus limiting the effect of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…This VRS method had already been used in other studies that evaluated propofol injection pain. 1517 The occurrence of pain was defined as any patient with a VRS greater than 0. When the clinical trial was finished, anaesthesia was induced by administration of propofol 1.5 mg kg −1 , fentanyl 5 μg kg −1 , and vecuronium 0.1 mg kg −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Much preliminary research has investigated the methods used to prevent or relieve propofol injection-related pain; these methods include nondrug approaches such as choosing a thicker vein (8), slowing injection speed (9), dilution (10,11), microfiltration (12), cooling the propofol (13), and topical EMLA use (14), as well as drug interventions, such as the use of lidocaine (15), opioids (16), sedatives (17,18), muscle relaxants (19), and nonsteroidal antiinflammatories (20,21), among others. A metaanalysis published in 2011 indicated that the most effective methods are selection of a thicker vein and prophylactic preinjection of lidocaine combined with vein occlusion (4).…”
Section: Discussionmentioning
confidence: 99%